Comparing the effectiveness of case-based technology-enhanced learning with face-to-face method - Hosseinali Khalili; Nahid Zarifsanaiey; Manoosh Mehrabi; Zahra Shayan (مجله ایرانی آموزش در علوم پزشکی, 2021)
Introduction: Technical advances highlight the need for dynamic strategies in medical training. Active medical education helps students sufficiently understand the real clinical situation. This study endeavored to compare the effectiveness of technology-enhanced Case-based Educational Intervention with In-person training on Knowledge and Satisfaction of Medical Students at Shiraz University of Medical Sciences. Methods: This study was an educational intervention with a post-test design on 584 medical students of clinical surgery departments (neurology and orthopedics) of Shiraz University of Medical Sciences in the academic year 2017-2019. The research samples were selected by convenience sampling and divided into intervention (case-based technology-based education) and control (scores of students participating in the previous in-person course) based on the non-random Consecutive sampling method. Data collection tools included a final exam in the surgical ward and a researcher-made questionnaire to assess the satisfaction of multimedia content. An independent t-test was used to compare the mean post-test knowledge score of the research samples. Results: The mean and standard deviation of knowledge score after the intervention in the intervention group (13.7±33.1 and 12.9±72.7) were not significantly different from the control group (13.62±2.7 and 13.27±2.7). Besides, 51% of students rated the quality of multimedia content as appropriate. Conclusion: The results revealed that case-based technology-based educational intervention leads to improved learning of medical students similar to face-to-face training. Due to the effectiveness, convenience, and low cost of this method, the use of this method is recommended for medical education in the clinical level.